2016
DOI: 10.5539/ijps.v8n2p111
|View full text |Cite
|
Sign up to set email alerts
|

Social Information Processing and Reactive and Proactive Aggression among Children with ADHD

Abstract: This study examined the social information processing qualities among children with reactive and proactive aggression among children with Attention Deficit Hyperactive Disorder (ADHD). It enrolled a total of 112 Saudi school children (62 boys, 50 girls; mean age = 9.26 years, SD = 1.98) of which 51 were diagnosed with ADHD and 61 typically developing peers. Data on children's social informational processing and type of aggression displayed were gathered and analyzed for group differences by diagnosis and gende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Difficulties in attention could, for example, lead children with ADHD to miss key social cues (e.g. that their behaviour is irritating a playmate), thus potentially leading to more instances where situations escalate to the point of an aggressive incident (Hammad & Awed, 2016). Alternatively, children with ADHD might successfully attend to social cues but then fail to encode them, undermining their ability to respond in a socially appropriate way (Andrade et al., 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Difficulties in attention could, for example, lead children with ADHD to miss key social cues (e.g. that their behaviour is irritating a playmate), thus potentially leading to more instances where situations escalate to the point of an aggressive incident (Hammad & Awed, 2016). Alternatively, children with ADHD might successfully attend to social cues but then fail to encode them, undermining their ability to respond in a socially appropriate way (Andrade et al., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research into links between aggressive behaviours and ADHD has mostly focused on associations at the disorder level (e.g. Bennett et al., 2004; Hammad & Awed, 2016; Slaughter et al., 2020) with a few studies also examining differences within the various dimensions of ADHD symptomatology, that is, predominantly hyperactive/impulsive, predominantly inattentive or combined ADHD presentations (Connor et al., 2010; Evans & Fite, 2019). One study examining the differential relations of proactive/reactive aggression and different ADHD subtypes found that proactive aggression was only more prevalent in children with combined inattentive and hyperactive/impulsive ADHD compared to a control group without ADHD, while both the combined subtype and the inattentive subtype showed higher reactive aggression than controls (Connor et al., 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Difficulties in attention could, for example, lead children with ADHD to miss key social cues (e.g. that their behaviour is irritating a playmate), thus potentially leading to more instances where situations escalate to the point of an aggressive incident (Hammad & Awed, 2016). Alternatively, children with ADHD might successfully attend to social cues but then fail to encode them, undermining their ability to respond in a socially appropriate way (Andrade et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research into links between aggressive behaviours and ADHD has mostly focused on associations at the disorder level (e.g. Bennett et al, 2004;Hammad & Awed, 2016;Slaughter et al, 2020) with a few studies also examining differences within the various dimensions of ADHD symptomatology, that is, predominantly hyperactive/impulsive, predominantly inattentive or combined ADHD presentations (Connor et al, 2010;Evans & Fite, 2019). One study examining the differential relations of proactive/reactive aggression and different ADHD subtypes found that proactive aggression was only more prevalent in children with combined inattentive and hyperactive/impulsive ADHD compared to a control group without ADHD, while both the combined subtype and the inattentive subtype showed higher reactive aggression than controls (Connor et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…As noted, the researches results on cyberbullying and traditional bullying among students with disability have confirmed several cases of verbal and physical abuse, as well as social rejection. Students with disability have more frequent targets of bullying than their peers without disability (Hammad & Awed, 2016;Maiano et al, 2016;Víllora et al, 2019).…”
Section: Introductionmentioning
confidence: 99%